2021
DOI: 10.3389/fneur.2021.782694
|View full text |Cite
|
Sign up to set email alerts
|

“ET Plus”: Instability of the Diagnosis During Prospective Longitudinal Follow-up of Essential Tremor Cases

Abstract: Background: A recent consensus statement introduced the term “ET plus”. Although investigators have quantified the prevalence of ET plus in cross-sectional studies, patients with ET plus have not been tracked longitudinally; hence, there is no understanding of its stability over time.Methods: We present prospective, longitudinal phenotypic data on an ET cohort that was followed regularly at 18-month intervals (T1, T2, T3, T4) for up to 64 months. We assigned an ET or ET plus diagnosis to each case at each time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“… 15 It should be noted, however, that the transition between syndromic allocations (ie, from ET to ET‐plus) can occur in the other direction (ie, from ET‐plus to ET because of the resolution of the soft signs). 16 This example highlights one of the novelties of the current classification, that is, the possibility that one syndrome might “evolve” over time into another. Tracking transitions across different tremor syndromes will eventually clarify the controversial relationship between them, for example between ET and ET‐plus or between ET and PD, 17 which is the reason why the idea of diseases with “antecedent ET” are described in the new classification.…”
Section: Clinical Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 It should be noted, however, that the transition between syndromic allocations (ie, from ET to ET‐plus) can occur in the other direction (ie, from ET‐plus to ET because of the resolution of the soft signs). 16 This example highlights one of the novelties of the current classification, that is, the possibility that one syndrome might “evolve” over time into another. Tracking transitions across different tremor syndromes will eventually clarify the controversial relationship between them, for example between ET and ET‐plus or between ET and PD, 17 which is the reason why the idea of diseases with “antecedent ET” are described in the new classification.…”
Section: Clinical Conceptsmentioning
confidence: 99%
“…Nonetheless, the construct of ET‐plus has generated an enlightened debate about its validity, 12,14 with some researchers proposing that it could represent a later stage of ET based on the evidence that its defining characteristics vary as a function of disease duration 15 . It should be noted, however, that the transition between syndromic allocations (ie, from ET to ET‐plus) can occur in the other direction (ie, from ET‐plus to ET because of the resolution of the soft signs) 16 . This example highlights one of the novelties of the current classification, that is, the possibility that one syndrome might “evolve” over time into another.…”
Section: Clinical Conceptsmentioning
confidence: 99%
“…Interestingly, the available longitudinal studies showed that no patients with ET + RT developed PD during a follow-up of 24–64 months (Gilmour et al 2021 ; Martinelli et al 1987 ; Bugalho et al 2021 ), but also that RT was an unstable feature, reverting from present to absent in more than one-third of cases (Iglesias-Hernandez et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, a few methodological considerations should be done. First, it seems in truth paradoxical that RT was found to fluctuate in a longitudinal study where it reverted from present to absent in more than one-third of cases (Iglesias-Hernandez et al 2021 ). This admittedly curious finding, in addition to selection biases (Louis et al 2015 ), might explain the discrepancies in prevalence of RT across the reviewed studies and might be partly due to the fact that RT in ET-plus can be observed in some conditions (while seated) but not in others (while standing) (Louis et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, it is worth noting that a diagnostic classification of "ET plus" has been proposed for cases in which the clinical manifestation of ET includes other mild neurologic signs of unknown clinical significance and some of the features reviewed herein (i.e., cognitive decline and motor symptoms, such as impaired gait and questionable dystonia) (5). However, there is controversy surrounding the use of ET plus as a diagnostic label (68)(69)(70). Much work remains to be done in terms of defining how various neurologic features arise at different points throughout the ET disease course and whether the emergence of such symptoms, in fact, represents an entity that is distinguishable from ET.…”
Section: Discussionmentioning
confidence: 99%